Young Carers’ Educational Experiences and Support: A Roadmap for the Development of School Policies to Foster their Academic Success - Lakman, Yana; Chalmers, Heather; Sexton, Cayleigh (Alberta Journal of Educational Research, 2017)
Young Carers (YCs) provide care for ill, disabled, or addicted family member(s) and may experience risk to their educational success. This study examined 145 YCs in Southern Ontario, aged 8-18, using surveys and found that many YCs considered school important and were doing well academically whereas some YCs’ education was negatively impacted. Correlational analyses revealed associations between caregiving time and missed school (r =.18, p = .030) as well as limit on future aspirations (r = .2120, p = .029). ANOVA analyses revealed that elementary-aged females placed higher importance on school than males (2 = .08, p = .036). Results also revealed that many YCs would use a variety of school services if offered, but over half would still prefer to maintain their caregiving role as a secret. Further findings and recommendations for supporting academic achievement are offered. Les jeunes aidants (YC – Young Carers) qui offrent des soins aux membres de leur famille qui sont malades, handicapés ou dépendants peuvent mettre à risque leur réussite éducative. Cette étude a porté sur 145 YC vivant dans le Sud de l’Ontario et âgés de 8 à 18 ans. À l’aide d’enquêtes, nous avons trouvé que plusieurs jeunes aidants considéraient l’école importante et réussissaient bien leurs études, mais que l’éducation de certains jeunes aidants était touchée négativement. Des analyses corrélationnelles ont révélé des associations entre le temps consacré à la prestation de soins et les absences à l’école d’une part (r =.18, p = .030) et les limites sur les projets d’avenir (r = .2120, p = .029). Des analyses ANOVA ont révélé que les étudiantes à l’élémentaire accordent une plus grande importance à l’école que leurs pairs masculins (2 = .08, p = .036). Les résultats ont également révélé que plusieurs YC profiteraient de divers services scolaires s’ils étaient offerts, mais plus de la moitié d’eux préféraient garder leur rôle d’aidant secret. Nous présentons d’autres résultats et offrons des recommandations pour appuyer les performances scolaires.